2019
DOI: 10.1038/s41467-019-11608-9
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria evoke alarm behaviour in zebrafish

Abstract: When injured, fish release an alarm substance (Schreckstoff) that elicits fear in members of their shoal. Although Schreckstoff has been proposed to be produced by club cells in the skin, several observations indicate that these giant cells function primarily in immunity. Previous data indicate that the alarm substance can be isolated from mucus. Here we show that mucus, as well as bacteria, are transported from the external surface into club cells, by cytoplasmic transfer or invasion of cells, including neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 70 publications
3
31
0
3
Order By: Relevance
“…Previous reports indicated that at least two glomeruli 240 in the lateral and medial olfactory bulb regions respond to the alarm substance [19,37]. 241 Present results indicate that the glomerulus in the lateral bulb (LG) is innervated by 242 microvillous olfactory sensory neurons [15]. The LG cluster consists of 2 identifiable 243 large glomeruli, LG 3 and LG 4 from 3 dpf onwards in the classification proposed by 244 Braubach et.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Previous reports indicated that at least two glomeruli 240 in the lateral and medial olfactory bulb regions respond to the alarm substance [19,37]. 241 Present results indicate that the glomerulus in the lateral bulb (LG) is innervated by 242 microvillous olfactory sensory neurons [15]. The LG cluster consists of 2 identifiable 243 large glomeruli, LG 3 and LG 4 from 3 dpf onwards in the classification proposed by 244 Braubach et.…”
mentioning
confidence: 72%
“…Supplementary Figure 5 Next, we examined the neural activity in the larvae. We first imaged the olfactory bulbs 137 of 5-7 day old Tg(gng8:GAL4, UAS:GCaMP6s) larvae where a small subset of olfactory 138 microvillus sensory neurons express GCaMP6s [44], and delivered Schreckstoff as 139 described previously [15,37]. A response to Schreckstoff was observed in the glomerular 140 termini of gng8-expressing neurons (Figure 2 A-C).…”
mentioning
confidence: 91%
“…The recording was started within 30 s of fish being in the recording tanks. For exposure to Schreckstoff, fish were placed in 100 mL beakers containing 200 µL of heated skin extract (see (Chia et al, 2019) for extraction method) in 50 mL fish facility water for 2 minutes.…”
Section: Novel Tank Assaymentioning
confidence: 99%
“…A growing number of studies have begun to address this gap in knowledge by characterizing the change in zebrafish swimming patterns in response to odors, identifying clear negative (avoidance) and positive (approach) chemotactic responses [4, 5, 7-12, 14, 15]. These studies investigated the behavioral responses to odors belonging to one or two of the following categories: food-related odors [7,8,21], social-related odors [9,13,29], decayrelated odors (polyamines in decomposing flesh) [30], and alarm odors [24,31,32]. This approach precludes the comparison of behavioral responses between all four odor categories within the same individual that is important to uncover stereotyped and odor-specific motor programs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, to our knowledge, the response to aversive decay-related odors and alarm odors was not compared in the same individual. Moreover, odor-driven behaviors were either measured in groups of fish, thus masking potential inter-individual variability in odor sensitivity or preferences [9,13,21,24], or the interindividual variability was not quantified [7,8,[30][31][32][33]. Therefore, there is an important need for measuring and analyzing the behavioral responses of individual fish to a broad range of odors, spanning the natural stimulus space.…”
Section: Introductionmentioning
confidence: 99%